Cromatografia líquida e análises quimiométricas na diferenciação química de acessos de Lippia alba (Mill) N. E. Brown e potenciais biológicos - Jesus, Raphael Amancio de (2018)
The methodology developed in the present work, through chromatographic fingerprint by LC-DAD and Principal Component Analysis (PCA), was adequate for the chemical differentiation of Lippia alba (Mill) NE Brown accessions, considering the extraction method (infusion and maceration hydroalcoholic) and the collection season (summer and winter), allowing to evaluate the influence of these variables on the chemical composition of extracts obtained. In addition, all extracts were submitted to cytotoxic tests against two tumor cell lines, HL-60 (human leukemia) and HepG2 (human hepatocellular carcinoma), and to inhibition tests against the enzyme acetylcholinesterase (AChE) in order to evaluate the form of extraction and which access is the most promising from a pharmacological point of view. Among the extracts analyzed against tumor cells, eight of them, two from the infusion: 01IW and 02IW and six from the hydroalcoholic extraction: 02HW, 24HW, 39HW, 54HW, 01HS and 24HS, presented better cell inhibition performances against HL-60, with percentage of inhibition between 40.0 and 52.0%, suggesting that these extracts are potentially promising against this lineage. With respect to the anticholinesterase tests, all extracts studied had low AChE inhibitory effect when compared to galantamine (87.4%), highlighting only the samples 01HW (28.4%), 02HW (27.2%), 54HW (29.3%), 01HS (32.7%), 02HS (27.4%) and 24HS (30.3%). Through the analyzes performed by Nuclear Magnetic Resonance (NMR) it was possible to identify the structures of some compounds isolated from this species: flavone tricin and phenylpropanoid verbascoside/isoverbascoside. In addition, the classes of three other metabolites were proposed: two phenylpropanoid derivatives and one flavonoid diglucoside.